DAERAH KEPULAUAN SEBAGAI SATUAN PEMERINTAHAN DAERAH YANG BERSIFAT KHUSUS - Stefanus, Kotan Y (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Some regions (local government) geograpically lie in islands area which get unjustice treatment compared with other regions. The problem is because of the service to public is broad and heavy in some islands, but do not get particular treatment from central government Search for and investigation about the law basis about archipelago area expresses that one of the principles of regional government undertaking according to the basic constitution of 1945 is that giving space to advance particular regions and specifically (including to as regions in islands). However, such principle has not been implicated broadly and clearly in the rule Law Number 32 years 2004. Key words: archipelago area, local government, particular regions, Legitimacy.